PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DIGITAL BERBASIS GUIDED INQUIRY MENGGUNAKAN LECTORA INSPIRE 18 DAN LIVEWORKSHEET PADA MATERI SISTEM KOLOID - Avischa Esty Wandani; Salastri Rohiat; Dewi Handayani (University of Bengkulu, 2022)
This development research aims to determine the level of feasibility and student response to the developed digital LKPD. The research was carried out in June-August 2021 at Bengkulu University and SMAN 08 Padang Jaya Bengkulu Utara. The development model used in this study is the ADDIE model which consists of 5 stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The sample used in this study was class XII IPA. The trial was conducted on a small scale with 12 students of class XII science. The research data was obtained from a validation questionnaire of material experts and media experts as well as student response questionnaires. From the results of the study, it was obtained that the feasibility level of digital LKPD in the material aspect was 85% with a very valid category. Meanwhile, the media aspect is 85,6% with a very valid category. The results of student responses to digital LKPD in small-scale trials obtained a percentage of 87.03% with a very interesting category. The results of this study indicate that the Digital LKPD developed is very feasible to be used in the learning process.